Continuous Evaluation of Evolving Behavioral Intervention Technologies - Mohr, David C. (2013)
Behavioral intervention technologies (BITs) are web-based and mobile interventions intended to support patients and consumers in changing behaviors related to health, mental health, and well-being. BITs are provided to patients and consumers in clinical care settings and commercial marketplaces, frequently with little or no evaluation. Current evaluation methods, including RCTs and implementation studies, can require years to validate an intervention. This timeline is fundamentally incompatible with the BIT environment, where technology advancement and changes in consumer expectations occur quickly, necessitating rapidly evolving interventions. However, BITs can routinely and iteratively collect data in a planned and strategic manner and generate evidence through systematic prospective analyses, thereby creating a system that can “learn.” A methodologic framework, Continuous Evaluation of Evolving Behavioral Intervention Technologies (CEEBIT), is proposed that can support the evaluation of multiple BITs or evolving versions, eliminating those that demonstrate poorer outcomes, while allowing new BITs to be entered at any time. CEEBIT could be used to ensure the effectiveness of BITs provided through deployment platforms in clinical care organizations or BIT marketplaces. The features of CEEBIT are described, including criteria for the determination of inferiority, determination of BIT inclusion, methods of assigning consumers to BITs, definition of outcomes, and evaluation of the usefulness of the system. CEEBIT offers the potential to collapse initial evaluation and postmarketing surveillance, providing ongoing assurance of safety and efficacy to patients and consumers, payers, and policymakers.